Efektivitas Ekstrak Daun Babadotan (Ageratum conyzoides L.) Dalam Menekan Pertumbuhan Cendawan Colletotrichum spp. Secara In-Vitro - Firdaus Firdaus; Noor Aidawati Aidawati; Dewi Fitriyanti Fitriyanti (www.ulm.ac.id, 2026)
Chili is an important horticultural crop that is cultivated in large quantities every day. However, production is often disrupted by diseases, one of which is anthracnose caused by the fungus Colletotrichum spp. Environmentally friendly control can be done with natural ingredients such as babadotan extract which contains antifungal compounds such as steroids, terpenoids, phenols, saponins, fatty acids and alkaloids. This research aims to test the ability of babadotan (Ageratum conyzoides L.) leaf extract to suppress the growth of Colletotrichum spp. in vitro. The research took place at the Phytopathology Laboratory, Faculty of Agriculture, Lambung Mangkurat University from October 2023 to May 2024. The method used RAL with 5 treatments and 4 replications. The results showed that BCE treatment (9% babadotan leaf extract) had the lowest growth inhibition at 40.02%, while BCB (3%) 34.94%, BCC (5%) 22.39%, and BCD (7%) 8.52%.